Numerical prediction of temperature distribution and residual stresses on plasma arc welded thin titanium sheets. (4th March 2021) - Arunkumar, M.; Dhinakaran, V.; Siva Shanmugam, N.
ABSTRACT: The residual stresses are responsible for most of the failure of weldments in nuclear industry and the temperature distribution is the key measure to predict these residual stresses. The residual stresses are produced due to the non-uniform heating and cooling of the material and thus generating inhomogeneous plastic deformation in the components during the welding process. The Plasma arc welded 2 mm thick Ti-6Al-4V plate is taken for the study to predict the weld bead geometry, temperature distribution and residual stresses. The temperature distribution is predicted through the transient thermal analysis in ANSYS Parametric Design Language (APDL) using Three-Dimensional Conical Heat Source Model & Dhinakaran's model and the simulated results are validated against the experimental outcomes. The temperature-dependent material properties with the temperature range varying from the room temperature to the melt pool temperature are considered for transient thermal analysis. The radiation heat transfer becomes predominant at high-temperature regimes; hence the radiation effects are imposed into the convective heat transfer coefficient. The weld bead geometry, temperature distribution and the residual stresses are predicted at various regimes of the plate. It is observed that the theoretical values obtained from the FEM Simulation are good in agreement with the experimental values.